Impact of teaching and learning styles on students' mathematics performance / Jong Li Ling, Ling Siew Ching - Li Ling, Jong; Ling, Siew Ching (2010)
The purposes of this study are to identify the lecturers' preferred teaching styles and students' preferred learning styles as well as to classify the students' preferred learning styles based on faculty and gender. This study also aims at determining the level of congruency between the teaching style and learning style across lecturers' classes. Furthermore, this study also examines the impact of students' learning styles and lecturers' teaching styles on the Mathematics performance of students. The Canfield Learning Styles Inventory (CLSI) and Canfield Instructional Styles Inventory (CISI) were adapted and administered to the students and their respective lecturers from the fundamental Mathematics courses of UiTM Sarawak.